Overview of the 36th International Conference, 36th Eg-MRS 202. Issue 1 (1st November 2022) - Aly, Arafa H.
Abstract : The overview describes the main directions and results of the 36 th Eg-MRS International Conference, 36 th Eg-MRS-2022 held in Cairo, Egypt, 24-25 September 2022. It gives the details about the participants and the proceedings. The Volume contains Proceedings of the 36 th Eg-MRS International Conference, Eg-MRS-2022: Modernization, Innovations and Progress" which was held in Cairo, Egypt in September 24-25, 2022.. The Conference held online using Zoom due to COVID-19. The purpose of the Conference is to share the results and prospects of the achievements in using advanced scientific, innovative and information technologies in materials sciences and its applications. In fact, this is the third year of publishing a special issue of Eg-MRS international conferences under the umbrella of IOP material sciences and engineering. The first one was in November 2019; Hurghada, Egypt [1]. The second and third was in August 2020 & July 2022 which was online due to COVID-19 [2, 3 ] All conference organizers/editors are required to declare details about their peer review. Therefore, please provide the following information: Type of peer review: Single-blind / Double-blind / Triple-blind / Open / Other (please describe) Double-blind Conference submission management system: Online: https://cutt.us/mo8G5 Number of submissions received: 50 Number of submissions sent for review: 30 Number of submissions accepted: 11 Acceptance Rate (Number of Submissions Accepted / Number of Submissions Received × 100): 22% Average number of reviews per paper: 3 Total number of reviewers involved: 20 Any additional info on review process: No Contact person for queries: Prof Arafa H.Aly; arafaaly@aucegypt.edu Please submit this form along with the rest of your files on the submission date written in your publishing agreement. The information you provide will be published as part of your proceedings.